Immediate Effect of Yoga Pranic Energisation Technique (YPET) on Heart Rate Variability and Pulmonary Function in Healthy Individuals – A Randomized Control Trial - Badigera, Shreedevi; Shreedhar, Bindu; Shetty, Shivaprasad; Shetty, Prashanth; Girishankara, Moodala (Indian Journal of Integrative Medicine, 2025)
Background: Pranayama are effective in improving autonomic and respiratory variables in Healthy and diseased individuals. Prana is one of the important in Pancha Pranas which regulates the function of the heart and lungs. Hence, we planned to conduct the effect of Yoga Pranic Energisation Technique (YPET) on heart rate variability (HRV) and pulmonary function (PF) on healthy individuals. Materials and methods: 250 subjects were screened from this 70 were randomly allocated to a study group (n = 35) for 30-minute YPET intervention and control group (n = 35), who received supine rest during. HRV and PF tests were assessed at baseline and immediately 5 minutes after the intervention. Results: There were no baseline differences across all parameters between the two groups. No significant difference was observed between group p > 0.05 in heart rate variable parameters. There was a significant increase in average RR (p = 0.003) and Standard deviation of all the R-R intervals (p = 0.004), with significant decrease in heart rate (p = 0.004) in the YPET group with only significant change of average RR (p < 0.001) was observed in control group. In pulmonary function test, there was a significant difference between the groups in forced expiratory volume in one second / Forced Vital Capacity (%) (p < .02), FVC (p < .001), and FEV1; p < 0.001. Conclusion: The study shown that practice of YPET could be beneficial in improving parameters of Heart rate variables and lung function parameters among healthy individuals.